2003
DOI: 10.1093/sleep/26.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy in Sleep Apnea: Instrument Development and Patient Perceptions of Obstructive Sleep Apnea Risk, Treatment Benefit, and Volition to Use Continuous Positive Airway Pressure

Abstract: These findings indicate that the SEMSA has strong psychometric properties and has the potential for identifying patient perceptions that may indicate those most likely to not adhere to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
1
7

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 51 publications
4
134
1
7
Order By: Relevance
“…12,13,30 Such educational interventions directed at patients may have played a role in previous findings of better PAP adherence in OSA patients managed by specialists. 7,8 Specifically, in patients with OSA being treated by PAP therapy, Weaver and colleagues demonstrated that three major cognitive factors play a role in adherence to PAP therapy-the patient's perception of health risk associated with OSA, the patient's expectations of outcomes, and the patient's perceived ability to use the PAP device.…”
Section: Patient Educationmentioning
confidence: 96%
See 2 more Smart Citations
“…12,13,30 Such educational interventions directed at patients may have played a role in previous findings of better PAP adherence in OSA patients managed by specialists. 7,8 Specifically, in patients with OSA being treated by PAP therapy, Weaver and colleagues demonstrated that three major cognitive factors play a role in adherence to PAP therapy-the patient's perception of health risk associated with OSA, the patient's expectations of outcomes, and the patient's perceived ability to use the PAP device.…”
Section: Patient Educationmentioning
confidence: 96%
“…7,8 Specifically, in patients with OSA being treated by PAP therapy, Weaver and colleagues demonstrated that three major cognitive factors play a role in adherence to PAP therapy-the patient's perception of health risk associated with OSA, the patient's expectations of outcomes, and the patient's perceived ability to use the PAP device. 13 All three of these factors can be favorably influenced by interventions that can deliver adequate patient education. 31,32 In our previous study, patient education leading to better patient perception of risk due to OSA was associated with better PAP adherence.…”
Section: Patient Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of unattended polysomnography, patients received the standardized educational session (previously described). At the time of CPAP delivery, patients completed a questionnaire about attitudes and beliefs about sleep apnea, social supports, and individual risks for consequences of sleep apnea and the Self‐Efficacy Measure in Sleep Apnea 12. The staff was trained to identify patient‐specific barriers and facilitators of CPAP adherence.…”
Section: Methodsmentioning
confidence: 99%
“…18 (e) Nasal congestion score (confounder): a validated questionnaire that assesses nasal congestion using a 5-point Likert scale that was previously administered to patients with sleep disordered breathing 19 and found to be associated with discontinuation of CPAP therapy. 15 This questionnaire was used to screen out patients who may be non-adherent due to excessive nasal congestion.…”
Section: Measurementsmentioning
confidence: 99%